Intuiciones visuales para pueblos olvidados. La utilización del cine en las Misiones Pedagógicas de la Segunda República Española - María García Alonso (Cahiers de Civilisation Espagnole Contemporaine)
The Pedagogical Missions were created with the goal of «bringing to people, with preference the ones who live in rural localities, the breath of the progress and the tools to participate in it». These missions were intended a prominent space to the cinematographer. Through the story of the screening and reception of the films, we will get closer to the experience of seeing the film for the first time in the rural Spain of the Second Republic.